Relation of kinematics variables and accuracy of shooting by upward leap for Oman's national handball team players - Kilani, H.; Alsulaimi, S. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The relations between kinematics variables and the accuracy of shooting by upward leap for players of Oman National Handball Team were investigated. Three digital JVC video cameras of 25 images per second were used to capture the two styles of shooting from jumping vertically with defense wall, and without defense wall on five players. APAS, MAXTRAQ system and KINOVEA software were used for motor analysis. Descriptive statistics, Pearson correlation, regression and t-test were used to treat the data. A direct relation between the take-off angle and accuracy of shooting was found. Correlations between kinematics variations of the shooting skills of upward leap were also found. Significant differences between shooting with and without defense in favor of shooting without defense during the takeoff flight vertically were also determined.